Hubungan Kecerdasan Emosional Dan Resiliensi Pada Remaja Yang Mengalami Putus Cinta di SMA Negeri 2 Denpasar - Sari, Luh Putu Nopi Diah Permata; Fridari, I Gusti Ayu Diah (Peneliti.net, 2024)
Psychological development of adolescents is characterized by emotional development, independence and personal maturity. One of the characteristics of adolescent psychological maturity is marked by the interest of adolescents with the opposite sex which will later be related to building love relationships. The breakdown of a romantic relationship will sometimes have an impact on an individual's ability to survive problems and overcome self-problems, which is often referred to as resilience. Therefore, in order to increase resilience within the individual, it is necessary to have the role of emotional intelligence to assist individuals in managing emotions. The purpose of this study is to see how the relationship between emotional intelligence and the resilience of adolescents who are experiencing a breakup in Denpasar City. This study used a correlational quantitative research method involving 143 students of SMA Negeri 2 Denpasar. The sampling technique utilized in this research is a non-probability sampling method known as purposive sampling. The Pearson correlation test results establish a level of significance in this study, which is equal to 0.000 (p< 0.05). Thus, it can be concluded that the variable of emotional intelligence holds a significant relationship with resilience. In addition, the correlation coefficient of the two variables is 0.559. the coefficients of emotional intelligence and resilience are positive, which indicates that there is a positive relationship between emotional intelligence and resilience, the higher the emotional intelligence, the higher the individual resilience.